Combination of Oketani and Rolling Massage to Increase Breast Milk Production - Rina Delfina; Sardaniah Sardaniah; Hermansyah Hermansyah (Universitas Islam Negeri Sumatera Utara, Medan, 2025)
Breast milk is the primary source of nutrition essential for infant growth and development. However, However, many mothers experience difficulties in breast milk production after childbirth, including first-time mothers lacking breastfeeding experience and those who have previously given birth. Several factors influence lactation, with breast care being a key determinant. Despite its importance, many postpartum mothers lack knowledge about proper breast care, leading to insufficient milk production that fails to meet their infants' needs. A combination of Oketani and rolling massage has been suggested as an effective intervention for enhancing milk production. The Oketani and rolling massage method is a specialized breast management technique known to improve milk production without causing discomfort. This study aimed to evaluate the effect of Oketani and rolling massage on increasing breast milk production among postpartum mothers at the Bengkulu City health center. The research employed a quasi-experimental design (pre-posttest with a control group), involving a sample of 60 postpartum mothers-30 in the intervention group and 30 in the control group. Breast milk production was measured before and after the intervention over five consecutive days. The findings, analyzed using the Mann-Whitney test, indicated a statistically significant effect of the intervention on breast milk production (ρ = 0.000 < α 0.05). Keywords: Breast Milk; Oketani Massage; Rolling Massage; Postpartum